2021
DOI: 10.29089/2021.21.00182
|View full text |Cite
|
Sign up to set email alerts
|

Spirometry in the prophylaxis of respiratory system diseases – a retrospective study

Abstract: Introduction: Diseases of the respiratory system are the third cause of mortality worldwide in terms of incidence. A spirometry test enables early detection of changes in the respiratory tract of persons with minor ailments, as well as the diagnosis of a fairly advanced illness whose symptoms have been neglected by the patient. Aim: The aim of this study has been to identify any irregularities in spirometry tests in the population of the province of Warmia and Mazury. Material and methods: The study covered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…Studies have shown that early assessment with a spirometry can help detect with early respiratory irregularities. 7 In regards to the choice of anesthesia, if the diagnosis of Poland syndrome had been made, adequate preparation can be made to reduce the risk of post operative recovery. Ideally regional anesthesia is the best modality, but in this case patient requires general anesthesia.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that early assessment with a spirometry can help detect with early respiratory irregularities. 7 In regards to the choice of anesthesia, if the diagnosis of Poland syndrome had been made, adequate preparation can be made to reduce the risk of post operative recovery. Ideally regional anesthesia is the best modality, but in this case patient requires general anesthesia.…”
Section: Resultsmentioning
confidence: 99%